Character Education: The State of Nigeria in Character Building - Uzoji Bright Kelechi; Muhammad Ridwan (Matondang Journal, 2025)
Education as a transformative tool for the growth and development of a nation cannot be overemphasized. Education is much more than the acquisition of literacy competencies ,it encompasses character modifications and character building which are necessary for producing a holistic individual that is able to make positive impact in the society where he lives.The main thrust of this paper is to examine the state of Nigeria in character building, focusing on the objectives and purposes of character education in Nigeria. The paper argued that character education instills a sense of responsibility in the younger generation which is key to ethical development ,social cohesion and personal wellbeing of the citizens.Hence concerted effort should be made by all and sundry towards promoting character education among the citizens.Finally,the paper ends with recommendations like; updating educational policies to integrate character education into the national school curriculum , encouraging ethical leadership at all levels ,encouraging families and communities in character education efforts which can reinforce moral values outside the classroom environment.